Differences in the Effect of Aerobic Exercise and Resistance Exercise on Cardiovascular Endurance in Metabolic Syndrome - Meryska, Refi; Khotimah, Siti; Wulandari, Rizky (Universitas Muhammadiyah Surakarta, 2025)
Introduction: individuals with metabolic syndrome have a three times greater chance of experiencing heart disease and stroke, twice as likely to experience death, and the risk of type 2 diabetes.Metabolic syndrome is characterized by a collection of metabolic disorders caused by obesity, in the form of a combination of dyslipidemia, hypertension, hyperglycemia, and central obesity.Objective to find out how aerobic exercise and resistance exercise differ on cardiovascular endurance. Methods: the research is quantitative with quasi experimental method, using pretest and posttest two group design. Sampling using purposive sampling by selecting samples from the population that meets the inclusion criteria. Results: most respondents were >70 years old (40%), female (65%), normal BMI (52.5%), and physical activity 2 times a week (47.5%).The results of the paired sample t-test in group 1 increased from 3.34 ± 0.57 to 6.00 ± 1.8. in group 2 increased from 3.38 ± 0.67 to 5.46 ± 1.14. the results of the independent sample t-test sig value (p = 0.025). Conclusion: there is an effect of aerobic exercise and resistance exercise, and there are differences in the effect on increasing cardiovascular endurance in metabolic syndrome.